2015
DOI: 10.3109/14756366.2014.1003928
|View full text |Cite
|
Sign up to set email alerts
|

Biological and computational evaluation of resveratrol inhibitors against Alzheimer’s disease

Abstract: It has been reported that beta amyloid induces production of radical oxygen species and oxidative stress in neuronal cells, which in turn upregulates β-secretase (BACE-1) expression and beta amyloid levels, thereby propagating oxidative stress and increasing neuronal injury. A series of resveratrol derivatives, known to be inhibitors of oxidative stress-induced neuronal cell death (oxytosis) were biologically evaluated against BACE-1 using homogeneous time-resolved fluorescence (TRF) assay. Correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Studies showed that Res and Res oligomers significantly inhibited BACE activity in a dose dependent manner, which was assessed by fluorescence resonance energy transfer (FRET) assay [ 30 ]. Similarly, Koukoulitsa et al found that Res and its derivatives bearing one ( tert -butyl, 1-ethylpopyl) or two bulky electron donating groups ortho to 4’-OH displayed different potencies against BACE1 using time-resolved fluorescence (TRF) assay, further suggesting that Res can inhibit BACE1 function [ 31 , 38 ]. In contrast, Marambaud et al found that Res does not inhibit Aβ production through neither affecting β- nor γ-secretases [ 39 ].…”
Section: Effect Of Res On Aβ Productionmentioning
confidence: 99%
“…Studies showed that Res and Res oligomers significantly inhibited BACE activity in a dose dependent manner, which was assessed by fluorescence resonance energy transfer (FRET) assay [ 30 ]. Similarly, Koukoulitsa et al found that Res and its derivatives bearing one ( tert -butyl, 1-ethylpopyl) or two bulky electron donating groups ortho to 4’-OH displayed different potencies against BACE1 using time-resolved fluorescence (TRF) assay, further suggesting that Res can inhibit BACE1 function [ 31 , 38 ]. In contrast, Marambaud et al found that Res does not inhibit Aβ production through neither affecting β- nor γ-secretases [ 39 ].…”
Section: Effect Of Res On Aβ Productionmentioning
confidence: 99%
“…For Parkinson's disease, ligand-binding to the SUR1 receptor (Santos et al, 2016 ) and the adenosine receptor (Zhang L. H. et al, 2014 ) was analyzed. Many targets were studied for Alzheimer's disease including β-secretase (Koukoulitsa et al, 2016 ), angiotensin-converting enzyme (Bhavaraju et al, 2016 ), acetylcholinesterase and butyrylcholinesterase (Kurt et al, 2017 ), and inhibitors directly targeting amyloid aggregation (Berhanu and Masunov, 2015 ). Ataxin-2 protein was studied for the treatment of spinocerebellar ataxia (Sinha et al, 2017 ), superoxide dismutase for amyotrophic lateral sclerosis (Zhuang et al, 2016 ), and Niemann-Pick type Cl and C2 proteins (Poongavanam et al, 2016 ) that occur in rare neurodegenerative diseases.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%
“…[43][44][45] Overall, although the MM/ PBSA method is able to estimate reasonable values of ligandbinding affinity, the absolute values do not correlate with the experiments. [46][47][48] In addition, another end-point free energy estimation approach, LIE, gives successful results to different systems. [49][50][51][52][53][54][55][56] In this approach, the binding free energy difference is computed based on the average of electrostatic and van der Waals (vdW) interaction energy differences of the inhibitor with its neighbouring atoms in various states involving the inhibitor in a solvated complex (bound statenoted as subscript b) and inhibitor in solvation (free statenoted as subscript f).…”
Section: Introductionmentioning
confidence: 99%